CONCEPT OF MICROBIOLOGY IN AYURVEDA - Ravneet, Chahal Kaur; Vikas, Saroch; Smita, Johar (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The science of Microbiology is not new to Ayurveda. Rig Veda (1/91/) highlights the concept of microbes as invisible organisms having specific unique characteristics. The literature of Vedic Microbiology paved the way to the existence of microbial world with the invention of a simple microscope in 1677 by Antoni Van Leewenhoeck. Classical Ayurvedic formulations are not only a supplement of diet but also an alternative in the treatment of bacterial infections. The paper attempts to review the implementation microbiological sciences in Ayurvedic research and development